2012
DOI: 10.1200/jco.2012.42.7732
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Plus Progestin and Colorectal Cancer Incidence and Mortality

Abstract: A B S T R A C T PurposeDuring the intervention phase in the Women's Health Initiative (WHI) clinical trial, use of estrogen plus progestin reduced the colorectal cancer diagnosis rate, but the cancers were found at a substantially higher stage. To assess the clinical relevance of the findings, analyses of the influence of combined hormone therapy on colorectal cancer incidence and colorectal cancer mortality were conducted after extended follow-up. Patients and MethodsThe WHI study was a randomized, double-bli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
70
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 97 publications
(78 citation statements)
references
References 39 publications
6
70
1
1
Order By: Relevance
“…When apoptosis was measured in the tumors of the ERbKO mice, it was found that E 2 treatment resulted in no significant change compared with the cholesterol-treated ERbKO mice. Similarly, data from human trials determining the effects of combined estrogen and progestin therapy in postmenopausal women showed that the combined HRT reduced the incidence of colon tumors in these women; however, the tumors that were detected were at a more advanced stage (Simon et al 2012). The fact that a similar phenomenon was observed in human tissues supports the results obtained from mice in this study.…”
Section: Discussionsupporting
confidence: 80%
“…When apoptosis was measured in the tumors of the ERbKO mice, it was found that E 2 treatment resulted in no significant change compared with the cholesterol-treated ERbKO mice. Similarly, data from human trials determining the effects of combined estrogen and progestin therapy in postmenopausal women showed that the combined HRT reduced the incidence of colon tumors in these women; however, the tumors that were detected were at a more advanced stage (Simon et al 2012). The fact that a similar phenomenon was observed in human tissues supports the results obtained from mice in this study.…”
Section: Discussionsupporting
confidence: 80%
“…2). It is important to note, however, that the progesterone receptor, under intense investigation in breast cancer 21 , may also be involved in cancer of non-reproductive organs, like what recently reported for lung NSCLC 22 and colon cancer 23 . a) Stem cell renewal : Specific ablation of estrogen receptor α, β and androgen receptor affects homeostasis and/or regeneration of organs unrelated to reproductive functions, such as lung 24, , colon 25 and skin [26][27][28] .…”
Section: Introduction (Epidemiology)mentioning
confidence: 78%
“…Observational studies have consistently found an association with hormone therapy use and lower colorectal cancer incidence (66, 67). With respect to colorectal cancer, in the estrogen plus progestin randomized WHI trial, there were 44% fewer colorectal cancers in the combined hormone therapy group diagnosedduring a mean of 5.6 years intervention (nominal p = 0.003) (68).…”
Section: Other Cancersmentioning
confidence: 99%
“…However, the cancers had more lymph node involvement (59% vs 29%, p = 0.003) and were diagnosed at substantially higher stage (regional/metastatic, 76% vs 49%, respectively, p = 0.004). Now with longer 11.6 years follow-up, there is a non-significant increase indeaths from colorectal cancer in the combined hormone therapy group (37 vs 27 deaths; 0.04% vs 0.03%: HR 1.29 95% CI 0.78-2.11, p = 0.320) (67). These data are not compatible with a clinically meaningful reduction in colorectal cancer since this disease carries a 30% 5 year mortality risk (69).…”
Section: Other Cancersmentioning
confidence: 99%